Power imbalances and equity in the day-to-day functioning of a north plus multi-south higher education institutions partnership: a case study - Silondile Luthuli; Marguerite Daniel; J. Hope Corbin (BMC, 2024)
Abstract Background Partnerships between Higher Education Institutions (HEIs) in the global north and south have commonly been used as a vehicle to drive global health research and initiatives. Among these initiatives, include health system strengthening, research capacity building, and human resource training in developing countries. However, the partnership functioning of many global north-south partnerships still carry legacies of colonialism through unrecognized behavior patterns, attitudes, and belief systems in how they function. Even with research literature calling for a shift from equality to equity in the functioning of these partnerships, many still struggle with issues of complex and unspoken power dynamics. To understand the successes and challenges of north-south partnerships, this paper explored partnership development and functioning of a northern and multi-southern HEIs partnership focused on nutrition education and research. Methods A qualitative research approach was used; data were collected through in-depth interviews (IDIs) with questions developed from the Bergen Model of Collective Functioning (BMCF). Thirteen IDIs were conducted with partners from all institutions including stakeholders. Findings The partnership was built on the foundation of experiences and lessons of a previous partnership. Partners used these experiences and lessons to devise strategies to improve partnership inputs, communication, leadership, roles and structures, and maintenance and communication tasks. However, these strategies had an impact on partnership functioning giving rise to issues of inequitable power dynamics. The northern partner had two roles: one as an equal partner and another as distributor of project funds; this caused a conflict in roles for this partner. The partners distinguished themselves according to partner resources - two partners were named implementing partners and two named supportive partners. Roles and partner resources were the greatest contributors to power imbalances and caused delays in project activities. Conclusion Using the BMCF to examine partnership dynamics illuminated that power imbalances caused a hierarchical stance in the partnership with northern partners having overall control and power of decision-making in the partnership. This could impact the effectiveness and sustainability of project in the southern institutions going forward.